Measurement properties of scores from a novel blind football assessment for adolescents with visual impairments - Adam Pennell; Emily Gilbert; Ali Brian; Pamela Beach; Lauren Lieberman (European Federation of Adapted Physical Activity, 2022)
Football (soccer) is one of the most popular sports for individuals with visual impairments (VI) worldwide but nascent within the United States (US). While there is burgeoning interest toward developing blind football at grassroot and national levels, particularly with the forthcoming 2028 Paralympics, no football-based talent identification or skill assessment has been developed or vetted in the US. Therefore, the purpose of this study was to investigate the immediate measurement properties of scores from a novel football assessment in amateur-skilled adolescents with VI in the US. Adolescents (n = 57) with VI physically completed the Blind Football Skills Test for Adolescents with VI (BFST-AVI) which was comprised of five football-related tasks. Scores were analyzed by item analyses, internal consistency, convergent validity, and construct validity procedures.  The results suggested that total and individual assessment scores had acceptable levels of reliability and validity. The BFST-AVI can be adopted immediately by grassroot organizations, national governing bodies, coaches, adapted and general physical educators, and associated practitioners for talent identification or general motor skill assessment purposes for amateur-skilled adolescents with VI.